Mechanisms of Arguments in the Prophet’s First Sermon after the Confession: A Man Does Not Lie to His Family - Al Tawalbeh, Ali M. (Dirasat: Human and Social Sciences, 2023)
Objectives: The study aims to reveal the argumentative mechanisms, values, and concepts embedded in the Prophet's sermon, and its rhetorical impact on enhancing the meaning and capturing the recipient's attention to the message's text. Methods: This study analyzes the argumentative verbal milestones in the Prophet's (PBUH) sermon from philosophical, rhetorical, and deliberate perspectives. It examines the introduction, semi-logical and reality-based arguments, as well as the role of argumentative links connecting ideas within the text. Additionally, it investigates the rhetorical, divine, and constructive methods, and their impact on enriching and persuading skeptical recipients of the new religion and messenger. Results:The study finds that this text, despite its brevity, is an argumentative text par excellence due to the presence of numerous argumentative mechanisms. It takes into account the eloquence level and acceptance of the argumentative message by the addressees. The researcher thoroughly studies and analyzes this text in its entirety, including letters, links, actions, and argumentative messages to achieve the desired result of this study. Conclusions: It is crucial to pay attention to rhetorical texts in general and the sermons of the Prophet (PBUH) in particular, to trace the rhetorical methods and argumentative mechanisms that persuade the addressees of the sermon's message.